Numerical simulations of flow and mass transfer during large-scale potassium dihydrogen phosphate crystal growth via three-dimensional motion growth method. (December 2018) - Wang, P.F.; Li, M.W.; Zhou, C.; Hu, Z.T.; Yin, H.W.
Highlights: Numerical simulations of large KDP crystal growth via a new method is carried out. The effects of some experimental variables on surface supersaturation are analyzed. The periodical reversed flow and shear stress enhance the morphological stability. Abstract: A novel solution-based crystal growth method, namely, the three-dimensional motion growth method (3D MGM) had been suggested by our team to effectively utilize convection for simultaneous enhancement of morphological stability and mass transfer. To evaluate this new method and link it to practice, numerical simulations of flow and mass transfer during large-scale potassium dihydrogen phosphate (KDP) crystal growth via this new method are carried out. The supersaturation field on the crystal surface is presented as functions of translational distance and crystal size. The relationships between directions of solution flow adjacent to crystal surface and surface shear stress are summarized and discussed. Results indicate that 3D MGM benefits the large-scale crystal growth by improving the morphological stability and crystal quality.